2018
DOI: 10.1186/s41938-017-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of white grubs (Coleoptera: Scarabeidae) with entomopathogenic nematodes in Rwanda

Abstract: White grubs are largely unsolved problems in vegetable and tuber production in East Africa. Novel Rwandan as well as international entomopathogenic nematodes (EPNs) were screened in nine laboratory bioassays and two small-scale field trials in 2014 and 2015. Soil-based laboratory bioassays revealed that all EPNs were able to infect Anomala graueri larvae (Coleoptera: Scarabeidae), although a relatively high number of infective juveniles were needed. Rwandan EPNs were as infectious as their corresponding intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…For instance, Youssef (2015) observed that with 3 dosages of 250, 500, and 1000 IJs/ml for S. carpocapsae, mortality rates of T. absoluta larvae reached to 80, 100, and 100%, respectively. A similar trend was obtained by Batalla-Carrera et al (2010), Mutegi et al (2017), Yuksel et al (2018), and Kajuga et al (2018) on various pests. This could be due to the fact that high number of EPNs would result in high number of symbiotic bacteria released in the host's body and thus enhanced killing speed owing to increase digestion of host tissues by toxins and hydrolytic enzymes secreted by these bacteria (Van Damme et al 2016).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…For instance, Youssef (2015) observed that with 3 dosages of 250, 500, and 1000 IJs/ml for S. carpocapsae, mortality rates of T. absoluta larvae reached to 80, 100, and 100%, respectively. A similar trend was obtained by Batalla-Carrera et al (2010), Mutegi et al (2017), Yuksel et al (2018), and Kajuga et al (2018) on various pests. This could be due to the fact that high number of EPNs would result in high number of symbiotic bacteria released in the host's body and thus enhanced killing speed owing to increase digestion of host tissues by toxins and hydrolytic enzymes secreted by these bacteria (Van Damme et al 2016).…”
Section: Resultssupporting
confidence: 87%
“…Kamali et al (2018). The local EPN isolates were able to kill T. absoluta and had even been found to be effective against white grubs in Rwanda (Kajuga et al 2018), while it was not easy to find EPNs which can kill them (Laznik and Trdan, 2015). Although EPNs live naturally in soil, different researchers found that they can be used on above-ground parts of the plant to control effectively the pests living in cryptic habitats like in leaf galleries (Batalla-Carrera et al In the present study, the third instar larvae were used; other studies revealed that EPNs were able to find and kill all the four larval instars inside or outside the leaf galleries (Batalla-Carrera et al 2010 andVan Damme et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations